THE USE OF INSTAGRAM AS A MEDIUM OF COMMUNICATION FOR THE CRYPTO COMMUNITY (A Case Study of the Indonesian Crypto Community on the @coinvestasi Account) - Tri Putra Ramadani Ibrahim; Sidiq Setyawan (UNIVERSITAS STEKOM, 2025)
This study explores the utilization of Instagram as a communication medium for the crypto community in Indonesia, focusing on the @coinvestasi account. The objective is to understand how Instagram functions as a platform for information sharing, education, and community interaction related to cryptocurrency and digital assets. The research employs a qualitative approach with a case study design. Data were collected through in-depth interviews with community representatives and followers, as well as documentation of Instagram content. The analysis was guided by the Circular Model of SoMe, which emphasizes four aspects: share, optimize, manage, and engage. The findings indicate that @coinvestasi uses Instagram strategically to deliver educational content, news updates, and interactive materials that attract and engage its audience. Various features such as feed posts, stories, reels, polls, and live sessions are utilized to encourage participation and foster two-way communication. The account successfully builds trust among followers by providing consistent, fact-based, and accessible information, while also creating opportunities for direct interaction and community growth. This research highlights the role of Instagram as an effective medium for building digital communities, particularly in emerging sectors such as cryptocurrency. The study contributes to the understanding of social media strategies in financial literacy and digital investment education, offering insights for practitioners, researchers, and community managers in leveraging social platforms for communication and engagement.